STATISTICAL AND MOTIVATIONAL MEASUREMENTS OF THE MANIFESTATIONS OF THE SACRED IN MODERN SOCIETY: Array - , Ю. І. (Municipal economy of cities. Series: «Economy science», 2018)
The author reveals the statistical and motivational aspects of faith and religion and their role in the life of contemporary man. The number of beliefs, religions, and denominations around the world (about 800), in addition to the number of theologies (over 200) proves how difficult it is for a person to find one's place in life through the use of extra-rational and non-discursive means. The advent of liberalism in all spheres of life has made religious faith marginal in both personal values and those of society overall reveals the duality of the moral and ethical system of man. Sociology provides a complex multi-valued image of relation to religious faith in modern Western society: the selectivity in the interpretation of the principles of faith, the reduction of the rank of faith in the hierarchy of values, the relativism in the approach to ethical norms - the lack of unambiguous criteria of good and evil. At the same time, the search for faith is revealed in stronger impressions, spiritual emotions and the deep experience of recollections and pilgrimages. People of the West are content with themselves and at the same time are looking for an identity in the realm of faith and beliefs. In Ukraine, the stage of extensive development of religious life has ended in favor of a moderate development of the religious and church network. The further development of the religious and church network will depend on the ability of the Church to meet the requirements of pastoral ministry in the modern environment. According to the numbers of religious churches, the Orthodox and Greek-Catholic Churches in Ukraine are mostly regional by character. Orthodox communities have survived in only two regions of Ukraine - in the Center and in the East. The increasing number and of religious schools and their students, as well as of the clergy, and the growing number of Sunday schools indicates that Protestant religious organizations are predominant in Ukraine. Keywords: sacred, society, statistics, motivation, Church and religious network